Mapping the Progress and Direction of Sustainable Agriculture Research in Indonesia: A Bibliometric Analysis Perspective - Sutiharni, Sutiharni; Mariay, Ivonne Fitria; Andriyani, Liz Yanti; Tuhumena, Veronica Leonora; Adlian, Adlian (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis aimed at mapping the progress and direction of sustainable agriculture research in Indonesia. With a focus on addressing environmental, social, and economic challenges while ensuring food security and agricultural productivity, sustainable agriculture has emerged as a critical area of focus globally. In Indonesia, a country rich in agricultural diversity and natural resources, sustainable agricultural practices are paramount to mitigate the impact of climate change, preserve biodiversity, and enhance the livelihoods of farmers and rural communities. Through systematic collection and analysis of relevant publications from academic databases, including Web of Science, Scopus, and Google Scholar, this study identifies key thematic areas, trends, collaboration networks among researchers, and potential research gaps within sustainable agriculture research in Indonesia. The analysis spans from 1982 to 2023, covering a wide range of topics such as agroecology, organic farming, precision agriculture, and sustainable resource management. Results reveal a significant impact of Indonesian research contributions, highlighting collaborative efforts and interdisciplinary approaches towards addressing complex agricultural sustainability challenges. The study provides valuable insights for policymakers, researchers, and stakeholders to prioritize areas for further development, formulate evidence-based policies, and foster interdisciplinary partnerships in promoting sustainable agricultural practices in Indonesia.